Configuration of a Magnetic Cloud From Solar Orbiter and Wind Spacecraft In-situ Measurements - Hu, Qiang; He, Wen; Zhao, Lingling; Lu, Edward (Frontiers in Physics, 2021)
Coronal mass ejections (CMEs) represent one type of the major eruption from the Sun. Their interplanetary counterparts, the interplanetary CMEs (ICMEs), are the direct manifestations of these structures when they propagate into the heliosphere and encounter one or more observing spacecraft. The ICMEs generally exhibit a set of distinctive signatures from the in-situ spacecraft measurements. A particular subset of ICMEs, the so-called Magnetic Clouds (MCs), is more uniquely defined and has been studied for decades, based on in-situ magnetic field and plasma measurements. By utilizing the latest multiple spacecraft measurements and analysis tools, we report a detailed study of the internal magnetic field configuration of an MC event observed by both the Solar Orbiter (SO) and Wind spacecraft in the solar wind near the Sun-Earth line. Both two-dimensional (2D) and three-dimensional (3D) models are applied to reveal the flux rope configurations of the MC. Various geometrical as well as physical parameters are derived and found to be similar within error estimates for the two methods. These results quantitatively characterize the coherent MC flux rope structure crossed by the two spacecraft along different paths. The implication for the radial evolution of this MC event is also discussed.